PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, MASA JABATAN CFO, DEBT COVENANT DAN GROWTH OPPORTUNITIES TERHADAP KONSERVATISME AKUNTANSI ( Studi Empiris Pada Perusahaan Go Public di Bursa Efek Indonesia Yang Berada Pada Sektor Non Finansial - Ristina Fauzia Bastiarso Putri; Rina Trisnawati (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Accounting conservatism is an act of prudence by recognizing losses or expenses that are likely to occur but do not immediately recognize future income or profits even though they are likely to occur. This study aims to analyze whether there is an effect of institutional ownership, managerial ownership, CFO tenure, debt dovenants and growth opportunities in publicly listed companies on the IDX in the non-financial sector for the 2018-2020 period. The population in this study amounted to 122 companies. The sampling technique used was purposive sampling method, and 366 companies were obtained as research samples for three years of observation (2018-2020). Multiple linear regression analysis was used as data analysis. The results of this study indicate that institutional ownership has no effect on the accounting conservatism variable; Managerial ownership has no effect on the accounting conservatism variable; CFO tenure has an effect on accounting conservatism variables; Debt agreements affect accounting conservatism variables; Growth opportunities affect the accounting conservatism variable.